2013
DOI: 10.1155/2013/183643
|View full text |Cite
|
Sign up to set email alerts
|

Medical Practices and Attitudes of Dual-Licensed Medical Doctors in Korea

Abstract: Unique dual medical system in Korea has resulted in the emergence of dual-licensed medical doctors (DLMDs) who have both traditional Korean medicine (KM) and Western medicine (WM) licenses. There have been few studies on DLMDs in spite of their growing number and importance within the medical system. We surveyed the current status and attitudes of DLMD to assess their role in integrative medicine. Questionnaires were administered to the members of the association of DLMD. Data from 103 DLMD were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We carefully reviewed previous studies [ 9 , 10 , 20 ] focusing on the attitude of medical doctors toward CAM, CP, and license unitarization for selecting questionnaire items. CP, license unitarization, and copractice were found to be the options for the integration between two medical paradigms in Korea.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We carefully reviewed previous studies [ 9 , 10 , 20 ] focusing on the attitude of medical doctors toward CAM, CP, and license unitarization for selecting questionnaire items. CP, license unitarization, and copractice were found to be the options for the integration between two medical paradigms in Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The survey questionnaires consist of three sections, 16 items. The first section has questions on the sociodemographic characteristics [ 9 , 21 ] such as gender, age, acquisition of clinical specialist, and practice setting. The second section has 7 items on the options for integration of medical services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent educational and practice systems exist based on exclusive license classifications in Korea. 19 Owing to this clinical situation, patients with chronic fatigue seem to visit TKM clinics not as a counterplan to conventional medicine but as the optimal choice among the possible treatments. From this study, we also found that the patient's belief was strong enough to endure the long-term and sometimes painful interventions such as burning injuries during TKM.…”
Section: Discussionmentioning
confidence: 99%
“…17 South Korea also has a unique healthcare system where Korean traditional medicine and Western medicine (including dental medicine) exist on equal terms with exclusive practice boundaries. 18 Moreover, South Korea does not exploit the family physician system, which means that the patients are free to select their primary care centres among a multitude of clinics and hospitals.…”
Section: Data Sourcementioning
confidence: 99%